PENGARUH PELAPISAN KITOSAN TERHADAP SIFAT FISIK DAN KIMIA BUAH MANGGA (Mangifera indica L.) KULTIVAR GEDONG GINCU - Adistye, Sandra; Budirokhman, Dodi; Saleh, Ismail (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2025)
Mango (Mangifera indica L.) is one of the most important tropical fruit commodities, highly favored both domestically and internationally for its distinctive taste and aroma. Indonesia is among the world’s top five mango producers in terms of production volume; however, its export value remains low due to limited postharvest quality and short shelf life. Gedong Gincu mango, a superior cultivar with attractive skin color as well as unique flavor and aroma, holds significant export potential. Nevertheless, as a climacteric fruit, it exhibits high respiration and ethylene production rates, leading to rapid deterioration. To address these challenges, postharvest technology is required, one of which is the application of edible coating using chitosan. Chitosan has been reported to extend shelf life by reducing respiration, minimizing transpiration, and maintaining vitamin C content and total soluble solids. This study employed a Completely Randomized Design with a single factor of chitosan concentration (0%, 1%, 2%, 3%, 4%, and 5%) and four replications. Parameters observed included weight loss, fruit firmness, vitamin C content, total soluble solids, and organoleptic attributes. The results indicated that chitosan concentration significantly affected the physical and chemical qualities of Gedong Gincu mango during storage. The 2% chitosan treatment showed the best performance, extending the shelf life up to 36 days, maintaining texture, and reducing deterioration compared to other treatments. Conversely, higher concentrations (4–5%) tended to induce surface fermentation. Thus, an appropriate chitosan concentration proved effective as a postharvest technology to enhance the quality and storability of Gedong Gincu mango, while also supporting its economic value and competitiveness in the export market.